Duration and ice thickness of a Late Holocene outlet glacier advance near Narsarsuaq, southern Greenland - Puleo, Peter J. K.; Axford, Yarrow (Climate of the Past, 2023)
Greenland Ice Sheet (GrIS) outlet glaciers are currently losing mass, leading to sea level rise. Reconstructions of past outlet glacier behavior through the Holocene help us better understand how they respond to climate change. Kiattuut Sermiat, a southern Greenland outlet glacier near Narsarsuaq, is known to have experienced an unusually large Late Holocene advance that culminated at ∼1600 cal yr BP and exceeded the glacier's Little Ice Age extent. We report sedimentary records from two lakes at slightly different elevations in an upland valley adjacent to Kiattuut Sermiat. These reveal when the outlet glacier's surface elevation was higher than during the Little Ice Age and constrain the associated outlet glacier surface elevation. We use bulk sediment geochemistry, magnetic susceptibility, color, texture, and the presence of aquatic plant macrofossils to distinguish between till, glaciolacustrine sediments, and organic lake sediments. Our 14C results above basal till recording regional deglaciation skew slightly old due to a reservoir effect but are generally consistent with regional deglaciation occurring ∼ 11 000 cal yr BP. Neoglacial advance of Kiattuut Sermiat is recorded by deposition of glaciolacustrine sediments in the lower-elevation lake, which we infer was subsumed by an ice-dammed lake that formed along the glacier's margin just after ∼ 3900 cal yr BP. This timing is consistent with several other glacial records in Greenland showing neoglacial cooling driving advance between ∼ 4500–3000 cal yr BP. Given that glaciolacustrine sediments were deposited only in the lower-elevation lake, combined with glacial geomorphological evidence in the valley containing these lakes, we estimate the former ice margin's elevation to have been ∼ 670 m a.s.l., compared with ∼ 420 m a.s.l. today. The ice-dammed lake persisted until the glacier surface fell below this elevation at ∼ 1600 cal yr BP. The retreat timing contrasts with overall evidence for cooling and glacier advance in the region at that time, so we infer that Kiattuut Sermiat's retreat may have resulted from reduced snowfall amounts and/or local glaciological complexity. High sensitivity to precipitation changes could also explain the relatively limited Little Ice Age advance of Kiattuut Sermiat compared with the earlier neoglacial advance.
Publisher: Copernicus GmbH

Younger Dryas and early Holocene climate in south Greenland inferred from oxygen isotopes of chironomids, aquatic Moss, and Moss cellulose - Puleo, Peter J. K.; Masterson, Andrew L.; Medeiros, Andrew S.; Schellinger, Grace; Steigleder, Regan; Woodroffe, Sarah; Osburn, Magdalena R.; Axford, Yarrow (Quaternary Science Reviews, 2022)
Ice core records have long indicated that the Younger Dryas began and ended with large, abrupt climate shifts over Greenland. Key climatic features remain unknown, including the magnitude of warming during the Younger Dryas-Holocene transition along with the seasonality and spatial variability of Younger Dryas climate changes across Greenland. Here, we use geochemical and paleoecological proxies from lake sediments at Lake N14 in south Greenland to address these outstanding questions. Radiocarbon dating and diatom assemblages confirm early deglaciation and isolation of Lake N14 before ∼13,600 cal yr BP, consistent with previous work. Oxygen isotope ratios (δ18O) of chironomid head capsules, bulk aquatic moss, and aquatic moss-derived cellulose are used to reconstruct oxygen isotopes of past lake water and annual precipitation. Oxygen isotope proxies indicate annual precipitation δ18O values increased by 5.9–7.7‰ at the end of the Younger Dryas. Following the Younger Dryas, moss and cellulose δ18O values show a clear decline in precipitation δ18O values of 2–3‰ from ∼11,540–11,340 cal yr BP that may correspond with the Preboreal Oscillation. Reconstructed precipitation δ18O values then gradually increased from 11,300–10,100 cal yr BP. All three aquatic organic materials register similar shifts in precipitation δ18O values over time, and they closely parallel the δ18O shifts observed in ice cores. This evidence strongly supports the utility of these methods for reconstructing lake water δ18O, and furthermore precipitation δ18O values where lake water reflects precipitation. The relatively large shift in isotopic composition of precipitation at Lake N14 suggests that shifts in temperature, precipitation seasonality, and/or moisture sources at the end of the Younger Dryas were even larger in south Greenland than they were in central Greenland, most likely because of the proximity to major changes in North Atlantic Ocean circulation. The annual air temperature change estimated at Lake N14 at the end of the Younger Dryas is also very large (∼18 ± 7 °C) compared to the summer warming previously inferred from chironomid species assemblages there (∼6 °C). This indicates that the strongest warming at the end of the Younger Dryas occurred in the winter season, consistent with past observations of intensified Younger Dryas seasonality at Lake N14 and elsewhere in Greenland.
Keywords: Chironomids; Deglaciation; diatoms; Greenland; Holocene; Micropaleontology; paleoclimatology; paleolimnology; Stable isotopes; Younger Dryas